Bioethics in Africa: A contextually enlightened analysis of three cases. Issue 2 (11th June 2021) - Jecker, Nancy S.; Atuire, Caesar
Abstract: Across sub‐Saharan Africa, bioethics is an emerging field of scholarly inquiry, informed by contextual features distinct to the region. A cultural mix comprised of Euro‐American influences, indigenous traditions, Christian faiths and Muslim communities, a bioethics for the sub‐Saharan region must be responsive to this milieu. This paper asks, what values and methods can best promote the practice of bioethics in Africa? We set forth a strategy that leans one way or another in response to contextual features of a particular setting. Since our aim is to be responsive to context, we begin with a series of cases and develop values and methods in response to each case as we work through its ethical analysis. Section I introduces a case involving setting priorities for public funding of services that produce large benefits for a small group of people, using the example of dialysis in Ghana. Section II presents a situation involving determining the permissibility of a double standard of quality for healthcare devices in rich and poor nations, using the example of explanting pacemakers from deceased people in wealthy nations for use by people in low‐ and middle‐income nations. Section III describes a scenario where international groups clash with religious and spiritual healers over the chaining of people with severe mental illness at prayer camps and healing centers in Ghana. Section IV articulates a three‐pronged strategy for engaging in bioethics brought to light by the case analyses and defends it against objections. Throughout the paper, we tag certain views 'African' and others 'Western' to indicate ethical beliefs commonly found in these regions and less commonly found elsewhere. We do not mean to imply that all Africans hold a certain ethical stance or that all Westerners do; nor do we mean to suggest that people outside these regions do not hold the views in question.